Start sites for bidirectional in vitro DNA replication inside the replication origin, oriC, of Escherichia coli. - Seufert, W (1987)
In vitro replication of mini-chromosomes in the absence of DNA ligase activity resulted in replication products with single-strand breaks at specific sites. The occurrence of these nicks was coupled to an active replication process, therefore we expect them to represent start sites for DNA replication. Two positions within oriC for each of the two leading strands of bidirectional replication were found. Within each position are one or two start sites. Counterclockwise synthesis started at positions 194/199 and 265/272, clockwise synthesis at positions 209/219 and 254. The start positions are located close to DnaA protein binding sites. A model for initiation accommodating this observation is discussed.